A Maternal-Effect Toxin Affects Epithelial Differentiation and Tissue Mechanics in Caenorhabditis elegans - Lehmann, Christina; Pohl, Christian (Frontiers in Cell and Developmental Biology, 2021)
Selfish genetic elements that act as post-segregation distorters cause lethality in non-carrier individuals after fertilization. Two post-segregation distorters have been previously identified in Caenorhabditis elegans, the peel-1/zeel-1 and the sup-35/pha-1 elements. These elements seem to act as modification-rescue systems, also called toxin/antidote pairs. Here we show that the maternal-effect toxin/zygotic antidote pair sup-35/pha-1 is required for proper expression of apical junction (AJ) components in epithelia and that sup-35 toxicity increases when pathways that establish and maintain basal epithelial characteristics, die-1, elt-1, lin-26, and vab-10, are compromised. We demonstrate that pha-1(e2123) embryos, which lack the antidote, are defective in epidermal morphogenesis and frequently fail to elongate. Moreover, seam cells are frequently misshaped and mispositioned and cell bond tension is reduced in pha-1(e2123) embryos, suggesting altered tissue material properties in the epidermis. Several aspects of this phenotype can also be induced in wild-type embryos by exerting mechanical stress through uniaxial loading. Seam cell shape, tissue mechanics, and elongation can be restored in pha-1(e2123) embryos if expression of the AJ molecule DLG-1/Discs large is reduced. Thus, our experiments suggest that maternal-effect toxicity disrupts proper development of the epidermis which involves distinct transcriptional regulators and AJ components.